(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
The history of science and technology in the Indian subcontinent begins with prehistoric human activity in the Indus Valley Civilization to early states and empires. Following independence, science and technology in the Republic of India has included automobile engineering, information technology, communications as well as space, polar, and nuclear sciences. The Indian civilization has a strong tradition of science and technology. Ancient India was a land of sages and seers as well as a land of scholars and scientists. Research has shown that from making the best steel in the world to teaching the world to count, India was actively contributing to the field of science and technology centuries long before modern laboratories were set up. Many theories and techniques discovered by the ancient Indians have created and strengthened the fundamentals of modern science and technology. While some of these groundbreaking contributions have been acknowledged, some are still unknown to most the early Vedic practices and subsequent Islamic influences gave a unique dimension to architecture in India. Indian construction technology is awe-inspiring. These are demonstrated in the form of a portable exhibit. The National Council of Science Museums received great support from Archaeological Survey of India in developing the concept of this particular exhibit. There is no doubt that Indian science is losing ground; every indicator shows this. The ranking of our top scientific educational institutions is consistently falling and our achievements are fewer by the day. Most importantly, Indian scientists are nowhere to be seen in the world you and inhabit. This is when our modern world requires science to be integrated into every aspect of daily life.